Seismic evidence of glacial-age river incision into the Tahaa barrier reef, French Polynesia - Michael R. Toomey; Jonathan D. Woodruff; Jeffrey P. Donnelly; Andrew D. Ashton; J. Taylor Perron (Marine Geology, 2016)
Abstract Rivers have long been recognized for their ability to shape reef-bound volcanic islands. On the time-scale of glacial–interglacial sea-level cycles, fluvial incision of exposed barrier reef lagoons may compete with constructional coral growth to shape the coastal geomorphology of ocean islands. However, overprinting of Pleistocene landscapes by Holocene erosion or sedimentation has largely obscured the role lowstand river incision may have played in developing the deep lagoons typical of modern barrier reefs. Here we use high-resolution seismic imagery and core stratigraphy to examine how erosion and/or deposition by upland drainage networks has shaped coastal morphology on Tahaa, a barrier reef-bound island located along the Society Islands hotspot chain in French Polynesia. At Tahaa, we find that many channels, incised into the lagoon floor during Pleistocene sea-level lowstands, are located near the mouths of upstream terrestrial drainages. Steeper antecedent topography appears to have enhanced lowstand fluvial erosion along Tahaa's southwestern coast and maintained a deep pass. During highstands, upland drainages appear to contribute little sediment to refilling accommodation space in the lagoon. Rather, the flushing of fine carbonate sediment out of incised fluvial channels by storms and currents appears to have limited lagoonal infilling and further reinforced development of deep barrier reef lagoons during periods of highstand submersion.
Keywords: Morphology